Mortal coil / 5. - Landy, Derek (Skulduggery Pleasant, 2010)
Valkyrie has discovered that she is Darquesse, the evil sorceress. The problem is, she doesn't feel she can tell Skulduggery, and so she must try to change her terrible destiny alone. But the price of changing your destiny is high, and if she fails, she'll die alone too ...